A novel CuO/TiO2 hollow nanofiber film for non-enzymatic glucose sensing. Issue 102 (20th October 2016) - Guo, Qiaohui; Zhang, Man; Li, Xia; Li, Xinrui; Li, Haoran; Lu, Yuanjie; Song, Xiaoxi; Wang, Li
Abstract : CuO nanoparticles loaded TiO2 hollow nanofibers with porous and hierarchically mesostructured nanostructure lead to excellent glucose biosensing. Abstract : A novel CuO nanoparticle-loaded TiO2 hollow nanofiber film (CuO/TiO2 ) was prepared by a simple and scalable electrospun nanofiber film template-assisted sol–gel method. In this facile method, the synthesis of TiO2 hollow nanofiber film and the loading of CuO nanoparticle were integrated into a single step. This porous and nanotubular CuO/TiO2 with well-dispersed CuO nanoparticles provides a well-defined hierarchical nanostructure for glucose oxidation. In application to glucose detection, CuO/TiO2 showed high electrocatalytic activity towards the oxidation of glucose in alkaline media, and a nonenzymatic glucose sensor was constructed. Under optimal experimental conditions, the designed sensor exhibited a wide linear range (0.02 to 19.26 mM, R = 0.996), which was wider than the precious CuO-based glucose biosensors. Additionally, the sensor showed high sensitivity, acceptable reproducibility and excellent selectivity. The novel textile formation, porous and hierarchically mesostructured nature of CuO/TiO2 with excellent analytical performances make it a superior platform for the construction of high-performance glucose biosensors.